2012
DOI: 10.1021/jm2013503
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and in Vitro Biological Evaluation of 1H-1,2,3-Triazole-4-carboxamide Derivatives as New Anti-influenza A Agents Targeting Virus Nucleoprotein

Abstract: The influenza virus nucleoprotein (NP) is an emerging target for anti-influenza drug development. Nucleozin (1) and its closely related derivatives had been identified as NP inhibitors displaying anti-influenza activity. Utilizing 1 as a lead molecule, we successfully designed and synthesized a series of 1H-1,2,3-triazole-4-carboxamide derivatives as new anti-influenza A agents. One of the most potent compounds, 3b, inhibited the replication of various H3N2 and H1N1 influenza A virus strains with IC(50) values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
99
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(103 citation statements)
references
References 30 publications
1
99
0
3
Order By: Relevance
“…Nucleozin-induced cytoplasmic aggregates of NP have been noted before but interpreted to be newly synthesized NP on the way into the nucleus (13,16,17). However, the timing of the effect we observed, as well as the inclusion of Rab11 in the aggregates (Rab11 interacts with RNPs but not non-RNP NP [6,9]), suggested that the drug was altering the trafficking of RNPs.…”
Section: Resultsmentioning
confidence: 49%
See 4 more Smart Citations
“…Nucleozin-induced cytoplasmic aggregates of NP have been noted before but interpreted to be newly synthesized NP on the way into the nucleus (13,16,17). However, the timing of the effect we observed, as well as the inclusion of Rab11 in the aggregates (Rab11 interacts with RNPs but not non-RNP NP [6,9]), suggested that the drug was altering the trafficking of RNPs.…”
Section: Resultsmentioning
confidence: 49%
“…Nucleozin aggregates outgoing viral RNPs (vRNPs) and Rab11 in the cytoplasm. Previous work has suggested two mechanisms of action for nucleozin: direct inhibition of RNP transcription, or a block to NP trafficking, postulated to be prior to nuclear import and RNP assembly (13,(15)(16)(17). However, neither mechanism seemed a plausible explanation of the late-acting drug effect, since vRNA synthesis, and therefore, by extrapolation, RNP formation, was near normal.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations